2003
DOI: 10.1196/annals.1254.003
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Channels and Synaptic Transmission at the Adult, Neonatal, and P/Q‐Type Deficient Neuromuscular Junction

Abstract: Different types of voltage-activated Ca(2+) channels have been established based on their molecular structure and pharmacological and biophysical properties. One of them, the P/Q-type, is the main channel involved in nerve-evoked neurotransmitter release at neuromuscular junctions and the immunological target in Eaton-Lambert Syndrome. At adult neuromuscular junctions, L- and N-type Ca(2+) channels become involved in transmitter release only under certain experimental or pathological conditions. In contrast, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 33 publications
6
39
0
Order By: Relevance
“…P/Q-type, N-type and, to some extent, R-type channels are highly expressed at presynaptic nerve terminals where their activities evoke neurotransmitter release (Katz et al 1996, Iwasaki et al 2000, Nudler et al 2003, Trimmer and Rhodes 2004.…”
Section: Fhm Type 3: Sodium Channels and Migrainementioning
confidence: 99%
“…P/Q-type, N-type and, to some extent, R-type channels are highly expressed at presynaptic nerve terminals where their activities evoke neurotransmitter release (Katz et al 1996, Iwasaki et al 2000, Nudler et al 2003, Trimmer and Rhodes 2004.…”
Section: Fhm Type 3: Sodium Channels and Migrainementioning
confidence: 99%
“…Peripheral side effects expected from autonomic and neuromuscular block. Bourinet et al, 1999;Nudler et al, 2003;Catterall et al, 2005bCatterall et al, , 2007 (For selectivity see Table 4.) Spider toxins: -agatoxin IVA Ca v 2.2 (CACNA1B) splice variants Brain, spinal cord, sympathetic neurons, DRG, contribution to presynaptic neurotransmitter release in CNS and PNS.…”
Section: None Known (Dihydropyridines)mentioning
confidence: 99%
“…The switch from N-to P/Q-type VGCCs, as the predominant calcium channel for neurotransmitter release in mature NMJ is associated with its closer localisation to release sites (Urbano et al, 2002;Nudler et al, 2003). This is in agreement with the study by Rosato-Siri et al (2002) which demonstrated ineffective binding of BAPTA, a fast calcium ion chelator to calcium ions that enter through P/Q-type VGCCs.…”
Section: Voltage-gated Calcium Channelssupporting
confidence: 80%
“…Thus, P/Q-type VGCCs and the direct interaction with laminin-β2 are necessary for efficient organisation of active zone elements. This could be due to the closer localisation of P/Q-type to release sites, being more favourable in interaction with presynaptic components in comparison with N-type VGCCs which are localised further away from the release sites (Urbano et al, 2002;Nudler et al, 2003) despite both VGCCs having direct interaction with presynaptic proteins such as Bassoon, SNAP25 and Syntaxin 1A (Kim & Catterall, 1997;Zhong et al, 1999;Chen et al, 2011;Nishimune et al, 2012).…”
Section: Failure In Switching Of N-to P/q-type Vgcc Clusters At Maturmentioning
confidence: 99%
See 1 more Smart Citation